Fiber fermentability effects on energy and macronutrient digestibility, fecal traits, postprandial metabolite responses, and colon histology of overweight cats - Fischer, M. M.; Kessler, A. M.; de Sa, L. R. M.; Vasconcellos, R. S. [UNESP]; Roberti Filho, F. O. [UNESP]; Nogueira, S. P. [UNESP]; Oliveira, M. C. C. [UNESP]; Carciofi, A. C. [UNESP] (Amer Soc Animal Science, 2012)
Considering the different potential benefits of divergent fiber ingredients, the effect of 3 fiber sources on energy and macronutrient digestibility, fermentation product formation, postprandial metabolite responses, and colon histology of overweight cats (Felis catus) fed kibble diets was compared. Twenty-four healthy adult cats were assigned in a complete randomized block design to 2 groups of 12 animals, and 3 animals from each group were fed 1 of 4 of the following kibble diets: control (CO; 11.5% dietary fiber), beet pulp (BP; 26% dietary fiber), wheat bran (WB; 24% dietary fiber), and sugarcane fiber (SF; 28% dietary fiber). Digestibility was measured by the total collection of feces. After 16 d of diet adaptation and an overnight period without food, blood glucose, cholesterol, and triglyceride postprandial responses were evaluated for 16 h after continued exposure to food. on d 20, colon biopsies of the cats were collected under general anesthesia. Fiber addition reduced food energy and nutrient digestibility. of all the fiber sources, SF had the least dietary fiber digestibility (P < 0.05), causing the largest reduction of dietary energy digestibility (P < 0.05). The greater fermentability of BP resulted in reduced fecal DM and pH, greater fecal production [g/(cat x d); as-is], and greater fecal concentration of acetate, propionate, and lactate (P < 0.05). For most fecal variables, WB was intermediate between BP and SF, and SF was similar to the control diet except for an increased fecal DM and firmer feces production for the SF diet (P < 0.05). Postprandial evaluations indicated reduced mean glucose concentration and area under the glucose curve in cats fed the SF diet (P < 0.05). Colon mucosa thickness, crypt area, lamina propria area, goblet cell area, crypt mean size, and crypt in bifurcation did not vary among the diets. According to the fiber solubility and fermentation rates, fiber sources can induce different physiological responses in cats, reduce energy digestibility, and favor glucose metabolism (SF), or improve gut health (BP).
Keywords: Cholesterol; colon mucosa; feline; Glucose; Short chain fatty acids; Triglycerides